Norcantharidin counteracts acquired everolimus resistance in renal cell carcinoma by dual inhibition of mammalian target of rapamycin complex 1 and complex 2 pathways in Vitro. Issue 1 (January 2022) - Chen, Xinglu; Cai, Xiangsheng; Zheng, Dianpeng; Huang, Xiuya; Chen, Ying; Deng, Tanggang; Mo, Lijun; Li, Hongwei; Li, Jinlong; Chen, Sansan
Abstract : Everolimus, an oral mammalian target of rapamycin complex 1 (mTORC1) inhibitor, presents a therapeutic option in metastatic renal cell carcinoma (RCC) patients who were intolerant to, or previously failed, immune- and vascular endothelial growth factor-targeted therapies. However, the onset of drug resistance limits its clinical use. One possible mechanism underpinning the resistance is that inhibiting mTORC1 by everolimus results in mTORC2-dependent activation of v-Akt murine thymoma viral oncogene (AKT) and upregulation of hypoxia-inducible transcription factors (HIF). Norcantharidin (NCTD) is a demethylated derivative of cantharidin with antitumor properties which is an active ingredient of the traditional Chinese medicine Mylabris. In this study, everolimus-resistant RCC cells (786-O-R) obtained by chronic everolimus treatment revealed higher level of HIF2α and over-activated mTORC2 pathway and NCTD inhibits cell proliferation in both everolimus-resistant and -sensitive RCC cells by arresting cell cycle in G0/G1 phase and reducing cell cycle-related proteins of C-Myc and cyclin D. Furthermore, NCTD shows synergistic anticancer effects combined with everolimus in everolimus-resistant 786-O-R cells. Mechanically, NCTD repressed both mTORC1 and mTORC2 signaling pathways as well as downstream molecular signaling pathways, such as p-4EBP1, p-AKT, HIF1α and HIF2α. Our findings provide sound evidence that combination of NCTD and everolimus is a potential therapeutic strategy for treating RCC and overcoming everolimus resistance by dual inhibition of mTORC1 and mTORC2.